Reconstruction of a Pancreatic Allograft With Variant Arterial Anatomy for Transplantation. Issue 2 (February 2019) - Adamson, Dylan; Holzner, Matthew L.; Wadhera, Vikram; Shapiro, Ron
Abstract : Abstract: Donor pancreas utilization rates remain low and aberrant donor anatomy can lead to organ discard by transplant centers. We report on a case of successful pancreas transplantation using a graft with variant arterial anatomy demonstrating that arterial reconstruction is a viable option if aberrant anatomy is encountered at the donor operation. Efforts must be made to use all pancreas grafts that are felt to be of appropriate quality.